Neuroglobin protects neurons against oxidative stress in global ischemia - Li, Richard Changxun (Nature Publishing Group, 2010)
Neuroglobin (Ngb) is a recently discovered globin that affords protection against hypoxic/ischemic-induced cell injury in brain. Hypoxic/ischemic injury is associated with accumulation of reactive oxygen species (ROS) and/or reactive nitrogen species (RNS). In previous studies, we found that Ngb has antioxidative properties, and protects PC-12 cells against hypoxia- and β-amyloid-induced cell death. To further delineate the potential role of Ngb in protection against cerebral ischemia–reperfusion injury in vivo, we developed a transgenic mouse line that overexpresses Ngb. Hippocampal ischemia–reperfusion injury was induced by a 10-minute bilateral occlusion of the common carotid arteries, and the animal brains were assessed 3 days later. CA1 neural injury was determined by cresyl violet staining. Lipid peroxidation was assessed using a malonyldialdehyde assay kit, whereas ROS/RNS accumulation was determined by Het staining in the CA1 hippocampal region. Hippocampal Ngb mRNA and protein expressions were assessed by reverse transcriptase-PCR and western blotting, respectively. Neuroglobin was successfully overexpressed in the hippocampus of Ngb transgenic mice. After ischemia–reperfusion, CA1 ROS/RNS production and lipid peroxidation were markedly decreased in Ngb transgenic mice compared with wild-type mice. Furthermore, CA1 neuronal injury was also markedly reduced. Thus, Ngb may confer protection against ischemia–reperfusion injury in the brain through its intrinsic antioxidant properties.